2020
DOI: 10.1186/s12889-020-09656-8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of anxiety among people living with HIV during the COVID-19 pandemic in Pune, India

Abstract: Introduction Globally, India has the third largest population of people living with HIV (PLHIV) and the second highest number of COVID-19 cases. Anxiety is associated with antiretroviral therapy (ART) nonadherence. It is crucial to understand the burden of anxiety and its sources among Asian Indian PLHIV during the COVID pandemic, but data are limited. Methods During the first month of government mandated lockdown, we administered an anxiety assessment via telephone among PLHIV registered for care at a publi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
0
28
1
2
Order By: Relevance
“…This finding is in line with a study done in Philippines nurses (37.8%) but lower than studies conducted in Bangladesh (87.7%), united Arab Emirates (46.9%), France(60.2%, and Iran(50.9%) [ 15 , 36 , 37 ]. However, this study is higher than a study done in India (25%) [ 13 ]. The variation could be difference in the study population and use of different measuring tool.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This finding is in line with a study done in Philippines nurses (37.8%) but lower than studies conducted in Bangladesh (87.7%), united Arab Emirates (46.9%), France(60.2%, and Iran(50.9%) [ 15 , 36 , 37 ]. However, this study is higher than a study done in India (25%) [ 13 ]. The variation could be difference in the study population and use of different measuring tool.…”
Section: Discussioncontrasting
confidence: 75%
“…Evidences suggested that individuals are experiencing high level of anxiety during COVID-19 [ 10 – 12 ].The psychological impact like anxiety, obsession and fear of Covid-19 varies across countries. For example, in India it ranges from 20%to 25% [ 13 , 14 ] a systematic review among health workers revealed that the pooled prevalence was 37% [ 5 ] Studies examined that sociodemographic the factors such as lower age, female sex, household income, and social support were the determinant factors of Anxiety and obsession [ 13 , 15 , 16 ]. Therefore, understanding and identifying the psychological impact and the contributing factors is vital to enhance preventive behavior of Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…A importância da geração de dados de saúde mental entre pessoas vivendo com HIV no cenário da pandemia pode ser inferida, visto que a piora da saúde mental foi relatada na população em geral. Na análise temática foram identificados os seguintes quatro temas: a) preocupações relacionadas com o presente imediato; b) preocupações relacionadas ao futuro iminente; c) falta de apoio social e financeiro; d) indiferença às circunstâncias secundárias ao COVID-19 (Marbaniang et al, 2020). Uma saúde mental equilibrada diminui os riscos de pouca adesão e abandono ao tratamento.…”
Section: Serviços De Hiv E a Pandemia De Covid-19unclassified
“…Numerous studies have demonstrated the elevated rates of depression, anxiety, and PTSD among living with HIV around the globe, due to reasons such as lack of social support( Collins et al, 2006 ; Jones et al, 2021 ; Tabler et al, 2021 ). There is also emerging evidence demonstrating the disproportionately high levels of depression and anxiety symptoms experienced by people living with HIV (PLWH) since the pandemic began( Jones et al, 2021 ; Marbaniang et al, 2020 ; Siewe Fodjo et al, 2020 ). In China, Sun et al found that PLWH reported high depressive and anxiety symptoms during the COVID-19( Sun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%